A first note on lichens of tawi wildlife sanctuary, Mizoram - P.C. LALREMRUATA,; R.C. LAHA,; LALHRIATPUIA,; ZOTHANMAWIA, (International Journal of Pharma and Bio Sciences, 2017)
The present study deals with the investigation of Lichen flora of Tawi Wildlife Sanctuary, Mizoram. In the present investigations a total of 60 species belonging to 19 genera and 9 families have been recorded for the first time from Tawi Wildlife Sanctuary, Mizoram. Out of which 18 species viz. Brigantiaea leucoxantha, Caloplaca ferruginea, Dirinaria consimilis, Graphis librata, Lobaria pseudopulmonaria, Lobaria discolor, Heterodermia pseudospeciosa, Hypotrachyna flexilis, Myelochroa subaurulenta, Pallidogramme chlorocarpoides, Pyxine cocoes, Pyxine consocians, Pyxine retirugella, Parmotrema chinense, Parmotrema cristiferum, Parmotrema pseudotinctorum, Parmotrema robustum, Pseudocyphellaria crocata are new records to Mizoram. Physciaceae, Graphidaceae and Parmeliaceae are the dominant families in the study area.